Folate receptor targeted chitosan and polydopamine coated mesoporous silica nanoparticles for photothermal therapy and drug delivery. Issue 12 (2nd December 2022) - Bhartiya, Prabha; Chawla, Ruchi; Dutta, Pradip Kumar
Abstract: The present work describes the folate receptor targeted chitosan and polydopamine coated mesoporous silica nanoparticles (CS-FA@PDA@MSN) for photothermal therapy and drug delivery. The developed therapeutic diagnostic nanocarrier is used to combat multidrug resistance of cancer in combination with photothermal effect. The nanocarrier exhibited high ability to transport quercetin (Q) into A549 cells through specific targeting ability via recognition through folate receptors expressed on cancer cells and stimulated drug release in its specific acidic environment. In addition, CS-FA@PDA@MSN-Q showed exceptional photothermal effect and as a consequence high cytotoxicity on A549 cells when stimulated by 808 nm laser. These outcomes may provide new possibilities and guidance for reversing multidrug resistance of cancer. GRAPHICAL ABSTRACT: UF0001